Effectiveness of Multisensory Instruction in Reading Skills of Grade 1 Pupils - Bautista, Kae Ann (Studies in Technology and Education, 2026)
This study determined the effectiveness of multisensory instruction in improving the reading skills of Grade 1 pupils at Bagu Elementary School, Pamplona, Cagayan during School Year 2024–2025. The research addressed the problem of low reading performance among beginning learners, particularly in word recognition and reading comprehension. A one-group pretest–posttest quasi-experimental design was employed involving twenty (20) Grade 1 pupils. The Philippine Informal Reading Inventory (Phil-IRI) served as the primary instrument in measuring reading performance before and after the five-week multisensory intervention. The multisensory instruction integrated visual, auditory, tactile, and kinesthetic activities such as tracing, phonics drills, guided reading, and story retelling to enhance learner engagement and retention. Results showed a notable improvement in pupils’ post-test mean scores in both word recognition and comprehension. The t-test for dependent samples revealed a statistically significant difference between pre-test and post-test results, leading to the rejection of the null hypothesis. The study concludes that multisensory instruction is an effective approach in strengthening early literacy skills and may serve as a valuable strategy for improving reading development among Grade 1 learners.